Overlap and Mutual Distinctions Between Clinical Recovery and Personal Recovery in People With Schizophrenia in a One-Year Study. (29th October 2021) - Dubreucq, Julien; Gabayet, Franck; Godin, Ophélia; Andre, Myrtille; Aouizerate, Bruno; Capdevielle, Delphine; Chereau, Isabelle; Clauss-Kobayashi, Julie; Coulon, Nathalie; D'Amato, Thierry; Dorey, Jean-Michel; Dubertret, Caroline; et al.
Abstract: Recovery is a multidimensional construct that can be defined either from a clinical perspective or from a consumer-focused one, as a self-broadening process aimed at living a meaningful life beyond mental illness. We aimed to longitudinally examine the overlap and mutual distinctions between clinical and personal recovery. Of 1239 people with schizophrenia consecutively recruited from the FondaMental Advanced Centers of Expertise for SZ network, the 507 present at one-year did not differ from those lost to follow-up. Clinical recovery was defined as the combination of clinical remission and functional remission. Personal recovery was defined as being in the rebuilding or in the growth stage of the Stages of Recovery Instrument (STORI). Full recovery was defined as the combination of clinical recovery and personal recovery. First, we examined the factors at baseline associated with each aspect of recovery. Then, we conducted multivariable models on the correlates of stable clinical recovery, stable personal recovery, and stable full recovery after one year. At baseline, clinical recovery and personal recovery were characterized by distinct patterns of outcome (i.e. better objective outcomes but no difference in subjective outcomes for clinical recovery, the opposite pattern for personal recovery, and better overall outcomes for full recovery). We found that clinical recovery and personal recovery predicted each other over time (baseline personal recovery for stable clinical recovery at one year; P = .026, OR = 4.94 [1.30–23.0]; baseline clinical recovery for stable personal recovery at one year; P = .016, OR = 3.64 [1.31–11.2]). In short, given the interaction but also the degree of difference between clinical recovery and personal recovery, psychosocial treatment should target, beyond clinical recovery, subjective aspects such as personal recovery and depression to reach full recovery.